A study the various clinical and electrophysiological parameters of severity of carpal tunnel syndrome, their correlation with post-operative recovery - Sushil Ramesh Nehete; Binita B. Raut; Amita S. Hiremath; R. Mukund Thatte (Indian Journal of Plastic Surgery)
Objective: We aimed to study the various clinical and electrophysiological parameters of severity of carpal tunnel syndrome (CTS) and to see if the severity of CTS affects recovery after surgery. Patients and Methods: A prospective study of 35 patients suffering from CTS. Clinical severity was assessed using visual analogue scale and standard questionnaires such as Levine and Disabilities of Arm, Shoulder and Hand questionnaires. All the patients underwent electrophysiological evaluation to assess electrophysiological severity of CTS. According to modified Padua classification, they were classified into three groups, namely, minimal to mild, moderate and severe to extreme. All patients underwent Carpal tunnel release in our unit. The clinical assessment was repeated 3 months post-operatively. Results: Out of 33 patients, majority (65.7%) of the patients were suffering from moderately severe CTS. The clinical provocative tests were positive in majority of patients. Clinically and statistically significant (P < 0.001) improvement was seen in all clinical severity scores. However, it did not show any statistical correlation with electrophysiological severity of the disease when compared among the groups. There was no association of age, gender of the patient, body mass index, hand dominance, affected side of the patient, results of provocative tests and the presence or absence of thenar muscle atrophy when compared among the three severity groups (P > 0.05). Conclusions: Although pre-operative clinical scores of severity and electrophysiology have a diagnostic role in CTS, they do not correlate with post-operative recovery and in turn fail to predict the extent of post-operative recovery before surgery.